Voyage to MARS - A Mobility Aware Recommender System - Ricardo Ferreira Leal dos Santos (2015)
Mobility is a concept that has been with humanity since its inception. Crucial to modern life, most people use mobility on a daily basis. It is a necessity. However, the over reliance on private transportation, cars in particular, over public transportation is having severe consequences on the environment. Carbon emissions, pollution and climate change are problems most cities are facing right now. This also causes a serious social and economic impact. It is of the utmost importance that we, as a society, work together to deal with this problem. The best way to do this is by promoting alternate modes of transportation like walking, cycling and, when those are not feasible, public transport. Previous work has shown that an effective way of promotion public transportation would be for public transport operators to cater to their passengers through the use of partnerships with local commerce and services using a system that would reward users for their use of public transportation. The more they use it, the more benefits they will reap. The work done in this thesis uses the concept of a recommender system to improve on that. A recommender system is a software tool or technique that provides suggestions to a user based on their characteristics, explicit or implicit interests, similar users preferences or items' attributes. The system conceptualized to manage this partnerships and harbor the reward system to foster public transportation is called Voyager. It is presented to passengers in the form of a mobile application for smartphones that will offer its users discounts, products or simply suggestions. Voyager will manage the interactions between public transport operators, providers and public transportation users. There will be various different types of offers available. "Reward offers" will be awarded to the user proportionally with their use of public transportation. Promotional offers will try to influence users to frequent new places as an effort to promote dead zones in the city. Other types of offers will have different goals like entertaining the user while he is waiting for the bus with, for example, an offer for a coffee in a coffee shop nearby. The implementation of Voyager would bring advantages to all major stakeholders. Public transportation users would be given offers and enjoy an overall better service. Public transport operators would have a new way of of encouraging passengers to use even more public transportation and have a way to unite all the different partnerships and campaigns in one place using an organized and easier to manage system. Providers would have access to the huge client-base of public transportation systems gaining a competitive advantage over similar businesses and an faster way to create campaigns either by offering discounts and products or promoting events, target the campaigns to a specific audience and track and evaluate the success of said campaigns. The biggest challenge of Voyager would be to attach the offers to the correct users: the ones who have interest in them. For the creation of a superior system, it is absolutely necessary the integration of a recommender system in Voyager. The recommender system developed for this project is called MARS: a mobility aware recommender system. MARS is able to recommend items to users based on their interests and their mobility profile. The tests conducted showed MARS does its job successfully and with a high degree of accuracy.